Young apple polyphenol extract prevents diabetic cognitive dysfunction by promoting TET2-mediated active DNA demethylation in the brain of diabetic mice - Jiacheng Fang; Jiacheng Fang; Xiaochen Zhang; Zhongshi Qi; Zhongshi Qi; Liying Zhou; Yuntiao Chen; Qingxin Li; Run Liu; Hongzhuan Yu (Frontiers in Nutrition)
IntroductionDiabetic cognitive dysfunction (DCD) refers to the impairment of cognitive function resulting from diabetes. The increasing prevalence of diabetes and the aging population have rendered DCD a significant threat to brain health. Young apple polyphenol extract (YAPE) has demonstrated potential in preventing DCD, although its underlying mechanism remains incompletely understood. Therefore, this study aims to investigate the preventive efficacy and underlying mechanisms of YAPE on DCD.MethodsStreptozotocin-induced diabetic mice were randomly divided into four groups (n = 15): the diabetes model group (DM), the metformin group (MET), the low-dose young apple polyphenol group (LYAP), and the high-dose young apple polyphenol group (HYAP). Meanwhile, 15 additional mice were assigned as the control group (CON).ResultsFollowing a 14-weeks intervention, disrupted cognitive function and neuronal apoptosis were observed in DM group, both of which were effectively restored by YAPE supplementation through improving ten-eleven translocation protein 2 (TET2)-mediated active DNA demethylation. Moreover, YAPE supplementation enhanced TET2 protein stability by activating phosphorylated AMP-activated protein kinase (AMPK) and improved TET enzyme activity by upregulating α-ketoglutarate/(succinic acid + fumaric acid) ratio, subsequently enhancing TET2 function.DiscussionConsequently, YAPE effectively delays progression from diabetes to DCD by facilitating TET2-mediated active DNA demethylation.